Autoregressive Distributed Lag Approach to the Income Inequality and Financial Liberalization Nexus: Empirical Evidence from Turkey - Özdemir, Onur (International Journal of Economics and Financial Issues, 2019)
This paper critically examines the validity of orthodox assumptions about the positive effects of financial liberalization on income inequality by employing the Autoregressive Distributed Lag (ARDL) Bound test by Pesaran et al. (2001) for the yearly data of Turkey over the 1987-2016 period. The benchmark results suggest that the income distribution worsens by the implementation of more liberalization in the financial sector for a long-run equilibrium relationship. Further, the study attempts to investigate an inverted U-shaped hypothesis of financial development. The findings indicate that income inequality improves at the initial stages of financial development but worsens over time. Therefore, it rejects the income-narrowing hypothesis for the latter stages of financial development. With the advantage that ARDL approach incorporates both I(0) and I(1) series, the study concludes that the positive relationship between financial liberalization and income inequality is prevalent both in the short- and the long-run in control of other variables. Keywords: Income Inequality, Financial Liberalization, Financial Development, Income Distribution, ARDL Bound Test JEL Classifications: F65, D31, C22 DOI: https://doi.org/10.32479/ijefi.8626